RANCANG BANGUN MESIN PRES BATAKO OTOMATIS MENGGUNAKAN SISTEM ELEKTRTO PNEUMATIK BERBASIS PLC DAN HMI - Juliandi Rachman, Muhammad (entries, 2024)
The high rate of infrastructure development in Pontianak City and Kubu Raya Regency will also impact the demand for construction materials, one of which is